ANALISIS PEMAHAMAN KONSEP IPA MATERI PERUBAHAN WUJUD BENDA KELAS V SD NEGERI 160 PALEMBANG - Fahreza, M. Aditya; A. Heryanto; Sunedi; Aditya Fahreza, M; Heriyanto, A. (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2024)
This research aims to determine the ability to understand science concepts regarding changes in the form of objects for class V SD Negeri 160 Palembang. The method used is descriptive qualitative. The data collection techniques used were interviews, observation and documentation. The results of teacher and student observations after researchers observed, understood and saw all learning activities taking place. The results of the interviews were reduced to strengthen the results of research observations. As for the results of these observations, the researcher really understands the models, media and methods that the teacher provides during the teaching process. Results of research with 7 informants from class V students and class V teachers, where for the ability to understand science concepts material changes in form. Class V objects at SD Negeri 160 Palembang can be categorized as good. Based on the results of interviews and observations, students seem to understand science learning, especially the material on changes in the shape of objects. Apart from that, observations of teacher test results showed that the average student score reached 74.6. This proves that the results of interviews, observations and documentation carried out by researchers show that students' memory is good.